LOGIKA FALLACY PENYELESAIAN SOAL CERITA PADA SISWA SEKOLAH DASAR - Andi Aswani; Irwan Akib; Rukli (STKIP Subang, 2023)
Logical fallacy refers to errors in constructing a logically valid reasoning within an argument, and it is prevalent among students. The purpose of this study is to examine logical fallacies in solving story problems among students using a single-subject design. The study adopts a qualitative research approach with an observational method. The researcher observes how students solve story problems in a naturalistic setting. Data is collected through task-based interviews, observations, and field notes. Single-subject participants from a fourth-grade class in elementary school are selected using purposive sampling technique. Data analysis utilizes thematic analysis to identify patterns of logical fallacies exhibited by the students. The findings of the study reveal correlation/causation fallacy in geometry statement problems. Students mistakenly link their lack of understanding regarding the difference between correlation and causation. It is crucial for students to comprehend that correlation merely indicates a statistical relationship between two variables, whereas causation involves a relationship where one event causes another. It is important to utilize sufficient data and evidence to support conclusions and avoid making erroneous causal assumptions. Furthermore, students tend to make errors in logical inference from the given information. They can be influenced by external factors such as biases, which can impact students' judgment in making inappropriate assumptions. In conclusion, three types of logical fallacies were identified, namely red herring, bandwagon fallacy, and correlation/causation fallacy, in the study.